The Role of Pentahelix Collaboration and Public Perception in Urban and Regional Planning and Sustainable Urban Development in Jakarta - Dananjaya, Ahmad Ghazy (Uniplan: Journal of Urban and Regional Planning, 2025)
Abstract: This study analyzes the effectiveness of urban and regional planning and sustainable urban development in Jakarta, focusing on Pentahelix collaboration and public perception. As a rapidly developing megacity, Jakarta faces complex urbanization challenges, including extreme population density, informal settlements, environmental degradation, and socioeconomic disparities. This research addresses a significant literature gap by integrating multi-stakeholder perspectives from the Pentahelix model"”government, academia, business, community, and media"”with public views. Employing an exploratory sequential mixed methods design (QUAL â†’ QUAN), the study begins with in-depth interviews with 10-15 Pentahelix stakeholders to explore key themes. These qualitative insights then inform the development of a quantitative survey administered to 400 respondents for generalization. Findings are expected to show 70âˆ’85% consistency between quantitative public perceptions and initial statements, critically enriched by qualitative insights. This research contributes evidence-based understanding for more relevant policy formulation and fosters effective sustainable urban development in Jakarta.